Effect of Milk Productive Seasons on Prolactin Hormone, Milk Composition and Metabolites in the Blood of Local Cows (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
productive  seasons  on  Prolactin hormone , milk composition and metabolites in the blood of  local cows. The study included 24 dairy cows during the second, third and fourth milk seasons . The results showed that the milk season was a significant effect (p